First Nations and Aboriginal Counsellor Education - Morrissette, Patrick J. (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper discusses contextual issues unique to First Nations and Aboriginal (FNA) undergraduate counsellor education. Although FNA and non-FNA student counsellors share similar educational experiences and needs, significant differences between these two groups require consideration and accommodation. This paper explores important features that influence student learning including student acclimatization, learning styles and participation, and the disclosure of cultural information.